(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the evolving nature of work and career development, highlighting the importance of strategic career planning for firstyear university students. It examines the impact of technological advancements, globalisation, and the rise of the gig economy on modern career paths. The article also emphasises the value of building practical skills and gaining real-world experience through internships, volunteering, and part-time jobs. Networking and mentorship are discussed as crucial factors for career success, alongside the need for lifelong learning in adapting to the fast-changing job market. Overall, the article provides essential strategies for young professionals to build a successful career in today’s dynamic work environment.